A distribuição espacial da indústria do vestuário no Brasil - Teixeira, Rudolph Fabiano Alves Pedroza [UNESP]; Bertella, Mario Augusto [UNESP] (Universidade Federal do Paraná, 2010)
This paper aims to analyse the spatial distribution of the Brazilian clothing industry in 1997 and 2006. In order to achieve this objective, this study used an exploratory spatial data analysis - ESDA. It was made a univariate analysis of the number of the existing clothing industries among Brazilian states. The null hypotheses of the spatial dependence absence was rejected and the construction of cluster maps showed two patterns: a high industrial concentration and a low one. On the other hand, a bivariate analysis was also conducted to permit a study between the number of clothing industries and the wage income of the neighbor regions. The result revealed spatial dependence besides similar cluster maps in both years. Therefore, two spatial patterns emerged: a high and a low industrial concentration. The final conclusion is that agglomeration economies are the main responsible for the results found in both analyses.

Este artigo faz uma análise da distribuição espacial da indústria do vestu- ário no Brasil para os anos de 1997 e 2006. Para tanto, além do referencial teórico, esse trabalho se utiliza das técnicas de análise exploratória de dados espaciais – AEDE. Destarte, foi realizada uma análise univariada para o número de indústrias de vestuário existentes entre os estados brasileiros. Rejeitou-se a hipótese nula de ausência de dependência espacial e a construção dos mapas de clusters indicaram padrões de alta e baixa concentração industrial. Por outro lado, também foi realizada uma análise bivariada, confrontando o número de indústrias de vestuário e massa salarial de regiões vizinhas. O resultado revelou dependência espacial, além de mapas de clusters similares para 1997 e 2006. Assim, dois padrões espaciais emergiram, um de alta e outro de baixa concentração industrial. Conclui-se que as economias de aglomeração são as grandes responsáveis pelos resultados encontrados em ambas as análises.
The spatial distribution of the Brazilian clothing industry
Keywords: Clothing industry; Exploratory spatial data analysis; Industrial clusters; Indústria do vestuário; Análise exploratória de dados espaciais; Concentração industrial